Relation between nitrogen fertilization and water soil conditions for a coffee plantation from Piracicaba, SP - Reichardt, Klaus; Silva, Adriana Lúcia da; Fenilli, Tatieli Anete Bergamo; Timm, Luís Carlos; Bruno, Isabeli Pereira; Volpe, Carlos Alberto (Coffee Science - ISSN 1984-3909, 1970)
Although the management of the coffee crop is well established in Brazil, there is still room for its improvement in relation natural resources available in each region, aiming the increase in productivity. Here are presented results regarding the fate of the fertilizer nitrogen (N) applied to a coffee plantation related to the prevailing soil water conditions. Soil water balances are discussed, which allowed evaluation of the root distribution, determinations of the crop coefficient and of the soil water conditions during the development of the crop. Approximately, 60% of the root system was distributed in the 0-0.3 m soil layer and the average crop coefficient was 1.1 for 3 to 5 year old plants. Using an N label, the 15N, it was possible to study the distribution of N in the plant and in the soil and establishes general N balances, which also include losses like leaching and volatilization. After two years of ammonium sulfate application, at rates of 280 (1st year) and 350 (2nd year) kg.ha-1 of N, in four equal application performed during the period of positive growth rate, the recuperation of fertilizer N were 19.1% by the aerial plant part and 9.4% by the roots, 12.6% remained in the soil and 11.2% in the litter; 0.9% was lost by volatilization and 2.3% by leaching; 26.3% was exported through harvesting and 18.2% remained in non evaluated compartments. From the applied 630 kg.ha-1 of N during the two years, 180 kg.ha-1 of N were found in the plant (shoot and root), which corresponds to 28.6%; 150 kg.ha-1 of N remained available for the next years (soil and litter), and only 20 kg.ha-1 of N were effectively lost (volatilization and leaching).